A Systematic Review of Implementing IoT Healthcare Systems: Technological, Organizational, and Ethical Barriers in Rural Settings - Mudzramer Hayudini; Angela Joy Jimpoy; Jonel Alibasa; Aisha Carolino; Jenden Julkamri; Nagdir Muhadja; Al Rajab H. Aming; Hamdoni Pangandaman; John Ed Augustus Escorial (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
The implementation of Internet of Things (IoT) technologies holds transformative potential for healthcare delivery in rural and underserved regions. This systematic review focuses on technological, organizational, and ethical barriers. A comprehensive literature search across six major academic databases yielded eleven empirical studies published between 2015 and 2025. The review adhered to PRISMA protocols, with data synthesized using the Synthesis Without Meta-Analysis (SWiM) guidelines. Findings revealed that technological challenges—such as unreliable internet connectivity, lack of device interoperability, and power supply issues—are widespread across rural implementations. Organizational limitations included inadequate training, resistance to workflow changes, and financial constraints. Ethical concerns primarily involved informed consent, data security, and privacy, often exacerbated by weak regulatory structures and digital illiteracy. Despite these obstacles, successful implementation efforts were marked by community engagement, phased integration strategies, and culturally adapted frameworks. The review underscores the necessity of comprehensive approaches that combine infrastructure development, workforce preparedness, and locally contextualized ethical safeguards. These findings provide a critical foundation for policymakers, system designers, and healthcare practitioners aiming to scale digital health solutions in low-resource settings.